Gestão de pessoas na Secretaria de Saúde do município de Tabatinga - AM - Ruiz, Maria da Silva (Brasil, 2022)
People are who move the whole organizational process of a company, be it public or private, the path for this company reaches - successfully - its stated goals, necessarily, entails valuing people who are involved in the organization. This Article has the pretension of diagnoses how the public managing is done at the Health Secretary of Tabatinga, located at western end of State of Amazonas, referring to permanent employees’s professional development. To propose practices to improve the managing processes of municipal people management that satisfy or minimize the existents problems. Verify the form of action used by people management about the professional development of its servants, as well as, quantify the level of satisfaction at workplace, dedication and employees engagement at the Health Secretary, focusing on human capital appreciation to meet the demands of society in a productive, transparent, effective and quickly manner, emphasizing under the auspices of modernity in Managing People in the public sphere, and implementation of favorable measures.